Comparison of chemical profiles and effectiveness between Erxian decoction and mixtures of decoctions of its individual herbs: a novel approach for identification of the standard chemicals. Issue 1 (December 2017) - Cheung, H.; Wang, S.; Ng, T.; Zhang, Y.; Lao, L.; Zhang, Z.; Tong, Y.; Chung, F.; Sze, S.
Abstract Background Identification of bioactive standard chemicals is a major challenge in the study of the Chinese medicinal formula. In particular, the chemical components may interact differently depending on the preparative methods, therefore affecting the amounts of bioactive components and their pharmacological properties in the medicinal formula. With the use of Erxian decoction (EXD) as a study model—a  well-known Chinese medicinal formula for treating menopausal symptoms, a novel and rapid approach in seeking standard chemicals has been established by differentially comparing the HPLC profiles and the menopause-related biochemical parameters of combined decoction of EXD (EXD-C) and mixtures of the decoctions of its individual herbs (EXD-S). Methods The levels of six chemicals, which exerted actions on the HPO axis, have been measured in EXD-C and EXD-S by HPLC. Twelve-month-old female Sprague-Dawley rats were employed and treated with EXD-C and EXD-S. Their endocrine functions after treatment were evaluated by determining the ovarian mRNA levels of aromatase, a key enzyme for estradiol biosynthesis. The effect of the antioxidant regimen was determined by the hepatic superoxide dismutase-1 (SOD), catalase (CAT) and glutathione peroxidase (GPx-1) mRNA levels. Results The amounts of mangiferine, ferulic acid, jatrorrhizine and palmatine in EXD-S were twofold higher than those in EXD-C. EXD-S was more effective in stimulating ovarian aromatase and the expression of the antioxidant enzymes compared with EXD-C. Conclusion Mangiferine, ferulic acid, jatrorrhizine and palmatine are suitable for use as standard chemicals for quality evaluation of EXD according to our approach. EXD-S could be more effective than EXD-C.